The Use of Suggestopedia to Develop Students’ Writing Skill in English : A Case of the Seventh Grade Students of SMP N 2 Mranggen in Academic Year 2014 / 2015 - Rizka Yuliani (Universitas PGRI Semarang, 2015)
This study is concerned with the improvement of the students’ mastery of writing skill of SMP N 2 Mranggen who are taught by using suggestopedia. The main objectives of this research are: (1) To find out the students’ writing ability, before being taught using suggestopedia method, (2) To find out the students’ writing ability, after being taught using suggestopedia method, (3) To find out the difference of the students’ writing ability, before and after being taught using suggestopedia method. This study is a pre experimental research, which uses one class as the experiment class in 7B of SMP N 2 Mranggen. The population of the research is the seventh grade students of SMP N 2 Mranggen. The writer used pre-test and post-test to find out the differences between the students’ research who were taught by suggestopedia in SMP N 2 Mranggen. The instrument of this research was essay test. The test was to measure students’ mastery of writing descriptive text in SMP N 2 Mranggen. There is significant difference in writing skill on descriptive text of the seventh grade students of SMP N 2 Mranggen in the academic year 2014 / 2015 after and before they had been taught by using suggestopedia. It can be seen from the result difference of ttest and ttable. The result of ttable and ttest is got 2,04 < 12,52 > 2,75. From this result ttest is higher than ttable.. In conclusion, teaching using suggestopedia to improve students’ writing skill is effective. The fact that, the students’ ability increased and they can make a descriptive text well. It means that using suggestopedia can help students to improve their writing skill.